Three-dimensional analysis of handspring with full turn vault: Deterministic model, coaches' belief and judges scores - Takei, Y. (Journal of Applied Biomechanics, 1998)
The purpose of the study was to identify mechanical variables that govern successful performance of the handspring with full turn vault. Subjects were 67 male gymnasts from 25 countries performing the vault during the 1992 Olympic Games. The vaults were filmed by two 16-mm Locam II DC cameras operating at 100 Hz. Approximately 80 frames per subject were digitized for each camera view. Direct linear transformation (DLT) was used to calculate the 3-D coordinates of the digitized body points. The method of Hay and Reid (1988) was used to develop a theoretical model to identify the mechanical variables that determine linear and angular motions of the vault. Significant correlations (p < .005) indicated that the following were important determinants for success: large horizontal velocity, large horizontal kinetic energy term, and overall translational kinetic energy term at takeoff from the board; short duration, small vertical displacement of the center of gravity (CG), and small somersaulting angular distance of preflight; large vertical velocity and large vertical kinetic energy term at takeoff from the horse; and large "amplitude of postflight," that is, large horizontal and vertical displacements of CG and long duration of flight; great height of CG during the second quarter-tum in postflight; and small point deduction for landing.